Question
upstudy study bank question image url

2) Realiza las siguientes operaciones con radicales: a) \( 3 \sqrt{2}-3 \sqrt{8}+3 \sqrt{18}= \) b) \( 7 \sqrt{54}-3 \sqrt{18}+\sqrt{24}-\frac{3}{5} \sqrt{50}-\sqrt{6}= \) c) \( \sqrt[3]{12} \cdot \sqrt{\frac{3}{4}} \cdot \sqrt[6]{\frac{12}{5}} \cdot \sqrt{\frac{15}{4}}= \) d) \( \sqrt[3]{3 \sqrt{9}}= \) e) \( \sqrt[4]{\frac{4}{3}}+\sqrt[3]{4}= \)

Ask by Dickson Patel. in Spain
Jan 07,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

a) \( 3 \sqrt{2} - 3 \sqrt{8} + 3 \sqrt{18} = 6 \sqrt{2} \) b) \( 7 \sqrt{54} - 3 \sqrt{18} + \sqrt{24} - \frac{3}{5} \sqrt{50} - \sqrt{6} = 22 \sqrt{6} - 12 \sqrt{2} \) c) \( \sqrt[3]{12} \cdot \sqrt{\frac{3}{4}} \cdot \sqrt[6]{\frac{12}{5}} \cdot \sqrt{\frac{15}{4}} = \frac{3 \sqrt[6]{675}}{2} \) d) \( \sqrt[3]{3 \sqrt{9}} = \sqrt[3]{9} \) e) \( \sqrt[4]{\frac{4}{3}} + \sqrt[3]{4} = \frac{\sqrt[4]{108} + 3 \sqrt[3]{4}}{3} \)

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Reviewed and approved by the UpStudy tutoring team

Beyond the Answer

Claro, vamos a resolver las operaciones con radicales. a) \( 3 \sqrt{2} - 3 \sqrt{8} + 3 \sqrt{18} = 3\sqrt{2} - 3(2\sqrt{2}) + 3(3\sqrt{2}) = 3\sqrt{2} - 6\sqrt{2} + 9\sqrt{2} = (3 - 6 + 9)\sqrt{2} = 6\sqrt{2} \) b) \( 7\sqrt{54} - 3\sqrt{18} + \sqrt{24} - \frac{3}{5}\sqrt{50} - \sqrt{6} \) Primero, simplificamos cada término: \( 7\sqrt{54} = 7(3\sqrt{6}) = 21\sqrt{6} \) \( -3\sqrt{18} = -3(3\sqrt{2}) = -9\sqrt{2} \) \( \sqrt{24} = 2\sqrt{6} \) \( -\frac{3}{5}\sqrt{50} = -\frac{3}{5}(5\sqrt{2}) = -3\sqrt{2} \) Entonces sumamos: \( 21\sqrt{6} + 2\sqrt{6} = 23\sqrt{6} \) Y para los términos en \(\sqrt{2}\): \( -9\sqrt{2} - 3\sqrt{2} = -12\sqrt{2} \) Finalmente, queda: \( 23\sqrt{6} - 12\sqrt{2} \) c) \( \sqrt[3]{12} \cdot \sqrt{\frac{3}{4}} \cdot \sqrt[6]{\frac{12}{5}} \cdot \sqrt{\frac{15}{4}} \) Para resolverlo simplificamos: \( \sqrt[3]{12} = 12^{1/3} = (3 \cdot 4)^{1/3} = 2^{4/3} \cdot 3^{1/3} \) \( \sqrt{\frac{3}{4}} = \frac{\sqrt{3}}{2} \) \( \sqrt[6]{\frac{12}{5}} = \left(\frac{12}{5}\right)^{1/6} = (12^{1/6} \cdot 5^{-1/6}) \) \( \sqrt{\frac{15}{4}} = \frac{\sqrt{15}}{2} \) Multiplicando, lo que se obtiene es un poco complicado, pero puedes utilizar propiedades de los exponentes para juntarlos y simplificar aún más. d) \( \sqrt[3]{3\sqrt{9}} = \sqrt[3]{3 \cdot 3^{1/2}} = \sqrt[3]{3^{3/2}} = 3^{1/2} = \sqrt{3} \) e) \( \sqrt[4]{\frac{4}{3}} + \sqrt[3]{4} = \left(\frac{4^{1/4}}{3^{1/4}}\right) + 4^{1/3} = \frac{\sqrt[4]{4}}{\sqrt[4]{3}} + \sqrt[3]{4} = \frac{2^{1/2}}{3^{1/4}} + 2^{2/3} = \sqrt{2}/\sqrt[4]{3} + 2^{2/3} \) Estas son las soluciones a las operaciones con radicales. ¡Espero que te haya divertido hacerlo!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy